Uncertainties in future climate predictions due to convection parameterisations - H. Rybka (Atmospheric Chemistry and Physics, 2014)
In the last decades several convection parameterisations have been developed to consider the impact of small-scale unresolved processes in Earth System Models associated with convective clouds. Global model simulations, which have been performed under current climate conditions with different convection schemes, significantly differ among each other in the simulated transport of trace gases and precipitation patterns due to the parameterisation assumptions and formulations, e.g. the computation of convective rainfall rates, calculation of entrainment and detrainment rates etc. Here we address sensitivity studies comparing four different convection schemes under alternative climate conditions (with doubling of the CO2 concentrations) to identify uncertainties related to convective processes. The increase in surface temperature reveals regional differences up to 4 K dependent on the chosen convection parameterisation. These differences are statistically significant almost everywhere in the troposphere of the intertropical convergence zone. The increase in upper tropospheric temperature affects the amount of water vapour transported to the lower stratosphere, leading to enhanced water vapour contents between 40% and 60% at the cold point temperature in the Tropics. Furthermore, the change in transporting short-lived pollutants within the atmosphere is highly ambiguous for the lower and upper troposphere. These results reflect that different approaches to compute mass fluxes, detrainment levels or trigger functions determine the transport of short-lived trace gases from the planetary boundary layer to lower, middle or upper tropospheric levels. Finally, cloud radiative effects have been analysed, uncovering a shift in different cloud types in the Tropics, especially for cirrus and deep convective clouds. These cloud types induce a change in net cloud radiative forcing varying from 0.5 W m−2 to 2.0 W m−2.